PECULIARITIES OF THE WORK OF THE GROUP "CREATING AUGMENTED REALITY" IN A REMOTE FORMAT - Slobodianyk, Olga (Physical and Mathematical Education, 2023)
Formulation of the problem. Modern realities and crises make their adjustments in all areas of our lives, so distance learning is already familiar. To date, there are many publications by scientists, and teachers-practitioners on the organization of the educational process online, describing methods of teaching various disciplines, taking into account their specifics. However, little attention is paid to extracurricular work during distance learning, in particular the work of circles. Therefore, the purpose of the article is: to consider the peculiarities of the organization of the work of the circle "Creation of augmented reality" in the remote format of the general secondary education institution.Materials and methods: methods of analysis and systematization of pedagogical, and methodological literature, generalization of the results of domestic and foreign experience on the use of immersive technologies in the educational process. Results. The features of the organization of the work of the circle include stages. At the preparatory stage, we focus students' attention on the theoretical aspects of augmented reality: we introduce a definition of the concept of "immersive technology", characterize AR, VR, and MR, determine the advantages and disadvantages of their use in various areas of our lives, consider the features of mobile applications for AR. The next stage is familiarization with the principles of operation of augmented reality tools (AR technologies are rapidly developing and depend on built-in sensors (accelerometer, GPS, compass), and the quality of the objects being played depends on the camera and photo applications, the resource of internal memory for data processing and artificial intelligence through voice commands. The third stage is the practical part, which includes the independent development of augmented reality objects in various environments, in particular, in Unity 3D, Blender, etc., and work with pak tools (RealityKit,  SceneForm, AR-Core, AR-Kit, Vuforia, etc.).Conclusions. For effective work of the club in a remote format, it is necessary to create a learning environment and provide: the possibility of conducting online lessons (synchronously or asynchronously); access to thematic electronic educational materials; the ability to send materials to students and receive completed tasks; feedback and evaluation. The learning environment can be Google Classroom. The classes of the club focus on the peculiarities of working in the Unity and AR Core environments.
Keywords: augmented reality; distance learning; extracurricular training; augmented reality objects